MEKANISME PERUBAHAN ANGGARAN DASAR YAYASAN - , ALAM DIKORAMA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Practice has conducted field work in the Office of Notary Agus Hanafi Muchammad SH, by observation and the observation mechanism Amendment Foundation in the office of Notary Agus Hanafi Muchammad SH Practice Job was done in order to determine the practice field after getting science theory in the lecture bench. This fieldwork practice delakukan from the date February 25, 2013 to April 20, 2013. In the office of Notary and PPAT Muchammad Agus Hanafi SH Job training is guidance, so that the process of doing dilakukkan amendments foundations can run in accordance with applicable regulations. The amendments require the consent and notification to the Ministry of Justice and Human Rights. As a form of mechanism made by a body corporate to be valid in the eyes of the law.